The Analysis of Politeness Strategy Used by The Main Characters in “Gifted” Film - Ayu Kadek Surya Maharani; Dewa Putu Ramendra; Ni Luh Putu Sri Adnyani (Universitas Muhammadiyah Kalimantan Timur, 2023)
Politeness strategy is a strategy in the use of language related to the use of good and polite verbal communication, which can make communication work cooperatively. In terms of communicating, politeness strategies are very important to avoid conflicts in communication which means avoiding face-threatening acts (FTA) of the hearer. In researching politeness strategy, the film is a work of art that can be analyzed because it has characters and utterances that can be analyzed and are closely related to real life. Thus, a film entitled